A potential controlling approach on surface ozone pollution based upon power big data - Xin Wang; Weihua Gu; Feng Wang; Li Liu; Yu Wang; Xuemin Han; Zhouqing Xie (SN Applied Sciences, 2022)
Article Highlights Surface ozone pollution in central China was investigated during the prevalence of the COVID-19 (2020.1–2021.5) NO2 and industrial VOCs contributing 33.72% and 21.12% to ozone formation Potential controlling pathway was proposed